Artificial Intelligence: Investigate the Implications of AI on the Work of the Holy Spirit, Including the Potential for AI to Facilitate or Hinder Spiritual Growth - Susan, Kemigisha (Advances in Social Sciences Research Journal, 2025)
This research investigates the implications of Artificial Intelligence (AI) on the work of the Holy Spirit and spiritual growth, examining the potential benefits and drawbacks of AI in facilitating or hindering spiritual development. A qualitative approach, combining literature review, case studies, and expert interviews, is employed to explore the intersection of theology, AI, and spirituality. Two case studies, the Interfaith Dialogue Platform and AI-Powered Chatbots in a Church Setting, provide valuable insights into the potential applications and implications of AI in spiritual contexts. The findings of this research contribute to the growing body of literature on the intersection of theology and AI, highlighting the importance of considering the implications of AI on spiritual growth and development. The study’s results have practical applications in various fields, including education, healthcare, and interfaith dialogue, and contribute to UNESCO’s 2030 Sustainable Development Goals, particularly Goal 16: Peace, Justice, and Strong Institutions.